Inclusion of Disabled Children in Indian Schools — Status and Need - Tandon, Garima; Singh, Sunil Kumar (THE PRIMARY TEACHER, 2017)
Each student is unique. Therefore, there must be no discrimination on the ground of class, creed, race, religion, colour, Intelligence Quotient (IQ) or ability, etc. In an educational setup, the term ‘inclusion’ is used for including and embracing this diversity without discrimination. One aspect of this diversity is ‘disability’. This article emphasises the educational status of Children With Special Needs (CWSN) in the Indian context. It deals with the present status of the disabled population, especially children, and various policies and programmes pertaining to their education and provisions for inclusion. The educational status of CWSN has been inferred from the Report of Ministry of Statistics and Programme Implementation (MSPI), titled ‘Disabled Persons in India: A Statistical Profile 2016’. The paper analyses that though various programmes and policies have been initiated from time-to-time, literacy rate among the disabled population is alarmingly low. Barriers regarding the inclusion of disabled children, drawn out of various studies, have been also highlighted in the paper. Besides, provisions for the inclusion of disabled children have been discussed. The article points out that meeting diverse needs is a challenge, but at the same time, it is an opportunity to enrich learning and school relations.